2023
DOI: 10.1097/fbp.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pharmacological activation of SERCA with CDN1163 affects spatial cognitive flexibility but not attention and impulsivity in mice

Benjamin Klocke,
Carter Moore,
Hayden Ott
et al.

Abstract: Intracellular calcium (Ca2+) homeostasis is critical for many neural processes, including learning, memory and synaptic plasticity. The sarco-endoplasmic reticulum Ca2+ ATPase (SERCA) is among the key regulators that preserve Ca2+ homeostasis in neurons. SERCAs comprise a set of ubiquitously expressed Ca2+ pumps that primarily function to sequester cytosolic Ca2+ into endoplasmic reticular stores. As SERCA has been implicated in the neurobiology of several neuropsychiatric and neurodegenerative diseases, pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Indeed, compelling evidence suggests that SERCA plays a critical role in brain physiology and pathophysiology; SERCA2 dysregulation has been associated with several neuropsychiatric disorders, including schizophrenia, bipolar disorder, cerebral ischemia, alcoholism, as well as Alzheimer’s and Parkinson’s diseases (for review see 17 , 62 ). Interestingly, recent studies from our group have revealed that chronic pharmacological stimulation of SERCA induces anxiety- and depressive-like behaviors, memory deficits, as well as sustained brain region-specific noradrenergic and serotonergic neurochemical alterations in mice, further highlighting the importance of dissecting the neurobiological implications of SERCA2-dependent Ca 2+ regulatory mechanisms in the brain 51 , 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, compelling evidence suggests that SERCA plays a critical role in brain physiology and pathophysiology; SERCA2 dysregulation has been associated with several neuropsychiatric disorders, including schizophrenia, bipolar disorder, cerebral ischemia, alcoholism, as well as Alzheimer’s and Parkinson’s diseases (for review see 17 , 62 ). Interestingly, recent studies from our group have revealed that chronic pharmacological stimulation of SERCA induces anxiety- and depressive-like behaviors, memory deficits, as well as sustained brain region-specific noradrenergic and serotonergic neurochemical alterations in mice, further highlighting the importance of dissecting the neurobiological implications of SERCA2-dependent Ca 2+ regulatory mechanisms in the brain 51 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity and attention were assessed using the 5-CSRTT in a 9-hole operant chamber using protocols provided by Lafayette Instrument Co (Lafayette Instrument Co., IN, USA) and based on previous studies from our lab and others 51 53 . Male and female control and cKO were housed throughout a reverse 24/h light/dark cycle, and all testing was performed during dark hours.…”
Section: Methodsmentioning
confidence: 99%